Variation in seed and seedling traits of the different ethno-varieties of jackfruit, a potential fruit tree species for food security - Ssali Nantongo, Judith; Mudondo, Scovia; Oluk, Richard; Agaba, Hillary; Gwali, Samson (Trees, Forests and People, 2022)
A key component of the performance of plant seeds is the germination capability as well as seedling survival and vigor. Seed traits from five jackfruit ethno-varieties (infra-specific diversity as understood and managed by farmers) were assessed. A greenhouse experiment was conducted to determine the survival of seeds, emergence and germination rate. Seeds from different ethno-varieties differed in their length (F (4,145) = 6.31, p < 0.001). The difference was highest between seeds from white, orange or yellow ethno-varieties. The width also slightly differed among ethno-varieties (F (4,145) = 3.29, p < 0.05). The average fresh and dry weights tended to be higher in seeds from the soft ethno-variety than the rest of the ethno-varieties. Differences in the survival of seeds and germination rate were also exhibited among ethno-varieties, where the white ethno-variety showed the highest pre-emergence mortality but at the same time the least germination time. Over the six-week period of germination, the soft ethno-variety exhibited the highest root:shoot ratio but also grew faster than all other ethno-varieties. There is potential evidence of phylogenetic constraints on seed size, germination and seedling vigor. Optimum growth for most of the traits was achieved between 6 and 7 weeks after sowing, which can guide on the time seedlings should be left in the pots before being transferred to the field. Further progeny tests should be undertaken on these provenances in the field over a longer period so as to obtain better distinction of the growth traits among the ethno-varieties.
Keywords: Seed; Seedling traits; Ethno-varieties; Jackfruit